Wisata Budaya Kawasan Cagar Budaya Nasional Muaro Jambi: Sejarah, Sosial Budaya, dan Kuliner Lokal - Nabila, Nabila; Agustina, Agustina; Efi, Agusti (Universitas Jambi, 2026)
The Muaro Jambi Temple National Cultural Heritage Area is one of the largest historical sites in Southeast Asia. This study examines the cultural tourism potential there, including its history, customs, traditional games, socio-cultural life, and local cuisine. The research method used was descriptive qualitative. Data were collected through observation, interviews, and literature review, then analyzed interpretively. The findings of this study indicate that Muaro Jambi Temple is not only an archaeological site, but also a living space for the community, upholding traditional Jambi Malay values. Local customs and traditions are still maintained. Traditional games are still played by children and adults, and traditional culinary delights are still served in homes and at traditional events. These elements coexist with tourism activities, not as additional decorations. This situation confirms that Muaro Jambi Temple has strong potential to become an educational cultural tourism destination while preserving the heritage still practiced by the community daily.